Faktor faktor yang mempengaruhi pemakaian alat kontrasepsi MKJP - Andry Simanullang; Rapael Ginting; Febry Mulyati; Tariana Ginting (Jurnal Kesmas Prima Indonesia, 2022)
The achievement of the use of MKJP contraceptives looks low for the working area of the birth control hall in Tanjung Seumantoh Village, Aceh Tamiang Regency in 2021. Based on DPMKPPKB data, MKJP contraceptive users only 22 pus active out of a total of 281 registered acceptors. The percentage of user success is only 17.6%, dominated by IUDs of 8.1% and MOW only 7.6%. This study was conducted to find out the picture of factors that affect the use of MKJP contraceptives in the working area of the Karang Baru District Birth Control Center of Aceh Tamiang Regency in 2021 This type of qualitative research is descriptive with a cross sectional approach. The study population is the entire acceptor of PUS MKJP as many as 22 people with a sample number of 18 people. From the results of the study, it was found that among the three factors: age, education, and parity, each has a relationship with the use of MKJP in Tanjung Seumantoh Village. Based on the age factor, it was found that the older a person is, the greater the possibility of using MKJP as a contraceptive. This acquisition is supported by reasons such as: first, the number of children has been sufficient and secondly, the age that does not allow return to add children. Furthermore, the educational factor, the average middle education (SMP-SMA) or elementary school prefers MKJP as a contraceptive. And finally the parity factor, that the greater the number of children born, it will affect the choice of acceptors to use MKJP contraceptives. This occurs in the birth rate ≥ 3, which is 3, 4, 5 and 6. Therefore, the three factors of age, education, and parity can affect acceptors in using MKJP in the working area of tanjung Seumantoh Village Kb Hall, Aceh Tamiang Regency.